The chosen few : how education shaped Jewish history, 70-1492 - Botticini, Maristella; Eckstein, Zvi (Princeton economic history of the Western world., 2012)
In 70 CE, the Jews were an agrarian and illiterate people living mostly in the Land of Israel and Mesopotamia. By 1492 the Jewish people had become a small group of literate urbanites specializing in crafts, trade, moneylending, and medicine in hundreds of places across the Old World, from Seville to Mangalore. What caused this radical change? "The Chosen Few" presents a new answer to this question by applying the lens of economic analysis to the key facts of fifteen formative centuries of Jewish history.